1971
DOI: 10.1002/pol.1971.150091121
|View full text |Cite
|
Sign up to set email alerts
|

Side‐chain crystallinity. II. Heats of fusion and melting transitions on selected copolymers incorporating n‐octadecyl acrylate or vinyl stearate

Abstract: synopsisThe heats of fusion and the melting transitions of the crystallinity present in the side chains were determined for selected copolymers incorporating n-octadecyl acrylate or vinyl stearate. A major purpose of this investigation was to ascertain the effect of INTRODUCTIONMuch interest has centeredl8.2 on the crystallization phenomenon in copolymers in which one co-unit of the main chain is capable of crystallizing. The Flory theory of the equilibrium crystallization of polymers3 required that sequence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 31 publications
0
84
0
Order By: Relevance
“…This tendency has been explained by difference in the mobility of the segmental motion of the main chain. 8 Melting temperature of the hexagonally-packed n-alkyl side chain is 10-40°C, which is higher and lower than the glass transition temperature, Tg, ofpoly(methyl acrylate) and poly(methyl methacrylate), respectively. Thus, the segmental motion of the main chain of PMx may be considerably restricted at the crystallization temperature of n-alkyl side chain.…”
Section: Effect Of Main-chain Structurementioning
confidence: 95%
See 1 more Smart Citation
“…This tendency has been explained by difference in the mobility of the segmental motion of the main chain. 8 Melting temperature of the hexagonally-packed n-alkyl side chain is 10-40°C, which is higher and lower than the glass transition temperature, Tg, ofpoly(methyl acrylate) and poly(methyl methacrylate), respectively. Thus, the segmental motion of the main chain of PMx may be considerably restricted at the crystallization temperature of n-alkyl side chain.…”
Section: Effect Of Main-chain Structurementioning
confidence: 95%
“…Heat of melting for the hexagonal modification of the n-alkane has been reported as 0. 73 kcal per mole of methylene unit, 8 • 2 5 then heat of transition for sixteen methylenes can be calculated as 11. 7 kcal mol -1 , which is comparable with the extrapolated value of !…”
Section: Effect Of Main-chain Structurementioning
confidence: 99%
“…22, No. 11,1990 St or MMA. 18 -22 Tgs increased almost linearly with the content of isopropenyltriazines in the copolymers.…”
Section: Glass Transition Temperaturesmentioning
confidence: 99%
“…11 Hirabayashi et al found the values of alternating comb-like copolymers to be 5.0 for OA-St, 2.7 for octadecyl methacrylate (OMA)-St, and 2.6 for OA-a-methylstyrene, respectively. 15 The copoylmers in this work gave Ne, smaller than those 982 of the conventional comb-like copolymers.…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation